Bank Risk and the Declining Franchise Value of the Banking Systems in the United States and Japan - Lee, Howard (IMF Working Papers; Working Paper ;, 1992)
This paper associates both the increase in risk taken by wholesale banks in the United States and the decline in earnings at wholesale banks in Japan with a reduction in the franchise value of wholesale banking. In contrast with the conventional view that relates the franchise value of banking to informational advantages over other lenders, this paper argues that banks' franchise value originates in their provision of liquidity and payments services to their customers. Therefore, the decline in corporate demand for bank liquidity is identified as a major factor explaining the fall of the franchise value. The paper also analyzes recent proposals for banking reform and assesses their relevance for dealing with the problems of wholesale banks.